K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 5 2019

=(\(4x^2-x^2+4x^2\) ) + (\(-3xy-xy\) )+ (\(y^2+2y^2+3y^2\) )

=(\(7x^2\))+(\(-4xy\))+(\(6y^2\))

2 tháng 2 2018

BÀI 2:

a)   Tại   x = 2;   y = -3   thì

                \(2.2^2-3. \left(-3\right)\)\(=8+9\)\(=17\)

b)   Tại  x = 2;  y = -3   thì

              \(\frac{1}{9}.2^3.\left(-3\right)^2-4.2\)\(=8-8\)\(=0\)

17 tháng 5 2016

1. G= 3x2y - 2xy2 + x3y3 + 3xy- 2x2y - 2x3y3

G = x2y + xy2 - x3y3 = xy (x + y -x2y2)  . Khi x= -2 . y=4 ta có G= -2*4( -2 + 4 - (-2)* 4) = 496

 

17 tháng 5 2016

a. B+A =( -2x2 + xy +2y2 -5x +2y - 3) + ( x-3xy -y2 +2x -3y +1)= -x2 - 2xy + y2 -3x -y -2 

A-B= -( -2x+xy + 2y2 -5x +2y -3) + ( x2 -3xy -y2 + 2x -3y +1) = 3x2 -4xy -3y2 +7x -5y +4

Tại x = -1, y =2

A= (-1)2 -3*(-1)*2 -22 +2*(-1) -3*2 +1 = -4

B= -2*(-1)2 + (-1)*2 + 2*22 -5*(-1) + 2*2 -3 = 10

6 tháng 5 2020

undefined

11 tháng 3 2017

=—11/4xy^2+2x^2y+6/5xy

11 tháng 3 2017

A=\(\left(3xy^2-2xy^2-4xy^2\right)+\left(2x^2y+\frac{1}{4}x^2y\right)+\left(xy+\frac{1}{5}xy\right)\)

A=\(-3xy^2+\frac{9}{4}x^2y+\frac{6}{5}xy\)

Bài làm

\(A=-2xy^2+\frac{1}{3}x^3y-x-\frac{1}{3}x^3y+xy^2+x-4x^2y\)

\(A=-xy^2-4x^2y\)

Bậc của đa thức là: 3